Experimental design, analysis and simulation of human-like hand tremor behaviour - As’Arry, Azizan (2009)
The purpose of this study is to investigate human hand tremor behaviour in postural condition. In order to achieve the objective, an experimental rig is fabricated as an apparatus to emulate the tremor behaviour. The experimental rig is designed to induce vibration along the dummy hand-arm in postural condition. In this study, an Intra Vernacular (IV) Training arm is used as the dummy hand-arm. Two DC motors are used to spin unbalanced masses as the source of excitation to the hand-arm. The quantitative assessment of human hand tremor and dummy hand-arm are mainly measured and recorded at the palm hand using light-weight accelerometer and displacement laser sensor. The accelerometer converts the physical movement to the acceleration signal. A laser displacement sensor is used for precise measurement due to its high sensitivity in motion. The laser is directly targeted at the palm hand, adjacent to the location of the accelerometer. The displacement and acceleration signals were then examined in time and frequency domains. In addition to that, a mathematical model of a four degree-of-freedom (DOF) system is introduced to represent the simulation biodynamic response (BR) of the palm of the human hand. Simulation results found that the tremor at palm hand occur at 9 and 12 Hz while the frequency of actual human hand tremor was observed at 9 Hz. From the findings, it is found that the fabricated experimental test-rig is capable to simulate the behaviour of human postural tremor at 9 Hz when the unbalancing mass rotate by the DC motors at the range frequency of 67.91 Hz to 77.80 Hz. Both results of the experiment and simulation can be used for further analysis of human hand tremor; typically Parkinson’s disease (PD) and this will help in the development of anti-tremor devices that can suppress tremor.